I am on the hit list : a journalist's murder and the rise of autocracy in India - Romig, Rollo (Penguin Books, an imprint of Penguin Random House LLC, 2024)
"A gripping investigation into the mysterious assassination of a journalist in India, revealing the courage and vulnerability of those who are fighting the decline of democracy around the world"--